2023
DOI: 10.32604/cmc.2023.033920
|View full text |Cite
|
Sign up to set email alerts
|

CE-EEN-B0: Contour Extraction Based Extended EfficientNet-B0 for Brain Tumor Classification Using MRI Images

Abstract: A brain tumor is the uncharacteristic progression of tissues in the brain. These are very deadly, and if it is not diagnosed at an early stage, it might shorten the affected patient's life span. Hence, their classification and detection play a critical role in treatment. Traditional Brain tumor detection is done by biopsy which is quite challenging. It is usually not preferred at an early stage of the disease. The detection involves Magnetic Resonance Imaging (MRI), which is essential for evaluating the tumor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Automatic segmentation and diagnosis of brain cancer using deep-learning techniques can save lives and prevent further tumor growth. Numerous approaches, such as those in [1][2][3][4][5][6], were implemented to segment brain tumors using medical images, such as CT scans and MRIs. Nevertheless, various developed models provided an average accuracy between 90% and 98%.…”
Section: Research Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Automatic segmentation and diagnosis of brain cancer using deep-learning techniques can save lives and prevent further tumor growth. Numerous approaches, such as those in [1][2][3][4][5][6], were implemented to segment brain tumors using medical images, such as CT scans and MRIs. Nevertheless, various developed models provided an average accuracy between 90% and 98%.…”
Section: Research Problemmentioning
confidence: 99%
“…In a study quite similar to this one, Mahesh et al in [4] developed a model to detect and classify BrT. Their study classified according to a tumor's location, identified using an extended Deep Convolutional Neural Network (DCNN) tool with feed-forward mode on MRIs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations